Local and distant response to intratumoral immunotherapy assessed by immunoPET in mice - Aurélien Marabelle; Louis Meyblum; Lambros Tselikas; Thierry de Baere; Sandrine Susini; Fréderic Deschamps; Baptiste Bonnet; Céline Chevaleyre; Benoit Jego; Dimitri Kereselidze; Vincent Lebon; Charles Truillet (Journal for ImmunoTherapy of Cancer)
Background Despite the promising efficacy of immune checkpoint blockers (ICB), tumor resistance and immune-related adverse events hinder their success in cancer treatment. To address these challenges, intratumoral delivery of immunotherapies has emerged as a potential solution, aiming to mitigate side effects through reduced systemic exposure while increasing effectiveness by enhancing local bioavailability. However, a comprehensive understanding of the local and systemic distribution of ICBs following intratumoral administration, as well as their impact on distant tumors, remains crucial for optimizing their therapeutic potential.To comprehensively investigate the distribution patterns following the intratumoral and intravenous administration of radiolabeled anti-cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and to assess its corresponding efficacy in both injected and non-injected tumors, we conducted an immunoPET imaging study.Methods CT26 and MC38 syngeneic colorectal tumor cells were implanted subcutaneously on both flanks of Balb/c and C57Bl/6 mice, respectively. Hamster anti-mouse CTLA-4 antibody (9H10) labeled with zirconium-89 ([89Zr]9H10) was intratumorally or intravenously administered. Whole-body distribution of the antibody was monitored by immunoPET imaging (n=12 CT26 Balb/c mice, n=10 MC38 C57Bl/6 mice). Tumorous responses to injected doses (1–10 mg/kg) were correlated with specific uptake of [89Zr]9H10 (n=24). Impacts on the tumor microenvironment were assessed by immunofluorescence and flow cytometry.Results Half of the dose was cleared into the blood 1 hour after intratumoral administration. Despite this, 7 days post-injection, 6–8% of the dose remained in the intratumoral-injected tumors. CT26 tumors with prolonged ICB exposure demonstrated complete responses. Seven days post-injection, the contralateral non-injected tumor uptake of the ICB was comparable to the one achieved through intravenous administration (7.5±1.7% ID.cm–3 and 7.6±2.1% ID.cm–3, respectively) at the same dose in the CT26 model. This observation was confirmed in the MC38 model. Consistent intratumoral pharmacodynamic effects were observed in both intratumoral and intravenous treatment groups, as evidenced by a notable increase in CD8+T cells within the CT26 tumors following treatment.Conclusions ImmunoPET-derived pharmacokinetics supports intratumoral injection of ICBs to decrease systemic exposure while maintaining efficacy compared with intravenous. Intratumoral-ICBs lead to high local drug exposure while maintaining significant therapeutic exposure in non-injected tumors. This immunoPET approach is applicable for clinical practice to support evidence-based drug development.